2012
DOI: 10.1186/1743-0003-9-72
|View full text |Cite
|
Sign up to set email alerts
|

The independence of deficits in position sense and visually guided reaching following stroke

Abstract: BackgroundSeveral studies have found correlations between proprioception and visuomotor function during stroke recovery, however two more recent studies have found no correlation. Unfortunately, most of the studies to date have been conducted with clinical assessments of sensation that are observer-based and have poor reliability. We have recently developed new tests to assess position sense and motor function using robotic technology. The present study was conducted to reassess the relationship between positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
190
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(197 citation statements)
references
References 63 publications
6
190
0
1
Order By: Relevance
“…1 Proprioceptive deficits affect more than half of stroke survivors [2][3][4] and can lead to significant problems with balance, 5 coordination, 6 and performance of activities of daily living. 4,7 Unfortunately, clinicians are faced with significant challenges to measure proprioception accurately, because clinical assessments of proprioception have been identified as insensitive, unreliable, and subjective. 8 We commonly see patients after stroke who are unable to perform activities of daily living, such as brushing their hair, or reaching for a cup; yet current clinical assessments make it difficult to discern whether the underlying problem is a result of damage to the motor system, sensory system, or both.…”
mentioning
confidence: 99%
“…1 Proprioceptive deficits affect more than half of stroke survivors [2][3][4] and can lead to significant problems with balance, 5 coordination, 6 and performance of activities of daily living. 4,7 Unfortunately, clinicians are faced with significant challenges to measure proprioception accurately, because clinical assessments of proprioception have been identified as insensitive, unreliable, and subjective. 8 We commonly see patients after stroke who are unable to perform activities of daily living, such as brushing their hair, or reaching for a cup; yet current clinical assessments make it difficult to discern whether the underlying problem is a result of damage to the motor system, sensory system, or both.…”
mentioning
confidence: 99%
“…For example, despite continued complaints of problems using a spoon and toothbrush, our subject's CMSA, a tool specifically developed for assessing arm and hand function, attained the maximal score at 6 months. Fundamental issues with the basic measurement properties of any given assessment can lead to problems in accurately identifying a subject's deficits [13]. In our study case, the robot and PPB scores, which are both based on normative scales identified impairments consistent with these problems in daily activities.…”
Section: Discussionmentioning
confidence: 82%
“…The relationship between our robotic measures and clinical measures is one of interest, but is difficult to evaluate quantitatively in a single case study. In a previous study, we evaluated a group of one hundred subjects with stroke and showed modest to moderate correlations between performance on various task parameters in the visually guided reaching or position matching tasks and common clinical measures such as the PPB and the FIM [13]. In that study the visually guided reaching parameters demonstrated a Pearson's correlation coefficient of 0.61 between the Movement Time parameter with the Purdue Pegboard, but only 0.35 with the Reaction Time parameter and no significant correlation with the robotic Posture Speed variable.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the incorporation of new robotic and advanced digital technologies has enabled more precise quantitative assessments of arm function. [1][2]3,4 The analysis of secondary submovements in chronic stroke survivors (SS) is important because on the one hand, increased frequency of submovements has been described in association with low movement speed which is also typical of aging and Parkinson's disease, 5,6 and on the other hand, the observed decrease in the frequency of submovements after therapeutic interventions has been proposed to characterize motor recovery after stroke. 7,8 Secondary submovements are present in neurologically intact individuals and their origin is a matter of debate.…”
Section: Introductionmentioning
confidence: 99%